2017
DOI: 10.1186/s12916-017-0974-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metabolic profiling of chronic low-grade inflammation among generally healthy individuals

Abstract: BackgroundInflammation occurs as an immediate protective response of the immune system to a harmful stimulus, whether locally confined or systemic. In contrast, a persisting, i.e., chronic, inflammatory state, even at a low-grade, is a well-known risk factor in the development of common diseases like diabetes or atherosclerosis. In clinical practice, laboratory markers like high-sensitivity C-reactive protein (hsCRP), white blood cell count (WBC), and fibrinogen, are used to reveal inflammatory processes. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 69 publications
(76 reference statements)
7
93
1
5
Order By: Relevance
“…Despite some different exclusion criteria, WBC associations replicated those from our previous publication 12 and were in part mirrored by PLT or MPV. Notably, this study clearly distinguishes from our previous work on inflammatory parameters, including WBC.…”
Section: Associations Between Blood Cell Measures and Plasma Metabosupporting
confidence: 79%
“…Despite some different exclusion criteria, WBC associations replicated those from our previous publication 12 and were in part mirrored by PLT or MPV. Notably, this study clearly distinguishes from our previous work on inflammatory parameters, including WBC.…”
Section: Associations Between Blood Cell Measures and Plasma Metabosupporting
confidence: 79%
“…LPCs activate signaling pathways promoting the release of second messengers, related to G protein-coupled receptors [186]. In obesity, significantly lower concentrations of most of the LPCs are detected [68], whereas LPCs concentrations were inversely correlated with the increased CRP levels [184]. Therefore, LPC could be useful early biomarkers to detect inflammatory states associated with MetS and related disorders.…”
Section: Lysophospholipidsmentioning
confidence: 99%
“…and external exposures (smoking, toxins, ionizing radiation, etc.). In order to regulate the reactive species, organism has endogenous antioxidant systems, or it obtains exogenous antioxidants from diet, that neutralizes these species and keeps the homeostasis of the body [68]. Production of free radicals and the resulting oxidative stress are part of the energy metabolism, emphasizing mitochondrial dysfunction in the development of disease.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Development of IR has been postulated to be linked with inflammation as additional pathogenic factors. Several inflammatory markers are showing clinical importance including C-reactive protein (hsCRP), white blood cell, fibrinogen and albumin [27,30]. However, previous studies found that C-reactive protein (CRP), a nonspecific marker of the inflammatory response, is most consistently associated with the development of IR and type 2 diabetes [10,11].…”
Section: Introductionmentioning
confidence: 99%